The chariot of Queen Zara - Abbott, Tony.; Merrell, David (New York : Scholastic, 2006)
Eric and his friends must use Queen Zara's chariot to rescue a wizard who is trapped on Droon's moon.
"A Little Apple paperback."
3.
007-010.
Accelerated Reader AR
Keywords: Droon (Imaginary place) -- Fiction; Wizards -- Fiction; Chariots -- Fiction; Rescues -- Fiction; Magic -- Fiction; Fantasy fiction